Theoretical Analysis of Urban Land Use Change by Information Provision for Nankai Trough Huge Earthquake in Japan - Yuzuru Miyata; Hiroyuki Shibusawa; Kentaro Mizuno (European Regional Science Association (ERSA), 2015)
This study employs an analytic urban economics approach, assuming that Toyohashi City takes a linear shape and there are two districts where the vulnerabilities to the earthquake in the two districts are different. That is, Toyohashi City is divided into two districts, one is safe for the earthquake while another one is risky for the earthquake. And then this study theoretically considers how the land rent and the land use pattern of these two districts will change by provision of disaster risk information and by a change in reliability of information for households. As a result, the following conclusions are obtained. (1) In a case where household subjective reliability of disaster risk information is not considered, households and land rents are uniformly distributed if disaster risk information is not provided, and the two districts receive the same damage when the earthquake occurs. However, if disaster risk information is provided, the land rent shows a decrease in the risky district as the frequency of earthquakes increases. On the other hand, the land rent increases in the district with the low damage risk. As a result, the land with the lower rent than the agricultural land rent is not used for residence, thus the residential area shrinks in the risky district while it expands in the safe district. From these results, provision of disaster risk information leads households in the risky district to the safe place, resulting in a decrease in the population and properties in the risky district that are expected to receive significant damage when the earthquake occurs. Moreover, since a decrease in the household utility due to an increase in the occurrence probability of the earthquake gets smaller than that in the case of symmetric vulnerability for the earthquake, it can be concluded that the effect of information provision becomes larger in the risky district.
Keywords: Q54; R14; R28; 330; earthquake; land use; bid rent; urban economics; Toyohashi